Classification Of Hadith Shahih Perspective Of Muhammad Al-Ghazali And Its Role For The Lives Of Muslims Today - Sayid Ahmad Ramadhan; Taufik Warman Mahfudz; Surya Sukti (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
The purpose of this paper is to discuss and review the fruits of Muhammad Al-Ghazali's thoughts on a hadith and its role in the lives of Muslims today. Literature research is used in the writing mechanism by tracing the scientific work of previous researchers and then analyzing and concluding. For the results of this paper, namely: 1. The method of determining the degree of hadith of Muhammad Al-Ghazali using criteria: a. testing with the Qur'an, b. testing with other hadiths, both the level and context of the content of the hadith, c. testing with historical facts (conditions when the hadith was issued), and d. testing concerning the conformity of reason (scientifically proven). 2. The role of hadith criteria set by Muhammad Al-Ghazali has had an impact on the understanding of Muslims, namely:: a. be more selective in responding to various hadiths circulating or in other words not necessarily take it for granted, b. Seeing the objectives, objectives, and intentions of a hadith by relating the explanation of the Qur'an then assisted by explanations that are not aimed at one scholar alone and adding a review of the truth of the ratio (reason) with scientific (science) and c. not fixated on judging a hadith because the narrator is considered qualified in the eyes of scholars, but tries to know and seek its truth through searches in scientific assemblies (ulama), scientific studies (writings), books of hadith. Keywords: Classification, Role, Shahih Hadith, Muhammad Al-Ghazali.